Protective effects of blocking PD-1 pathway on retinal ganglion cells in a mouse model of chronic ocular hypertension - Sheng, Siqi; Ma, Yixian; Zou, Yue; Hu, Fangyuan; Chen, Ling (Frontiers in Immunology, 2023)
Purpose: In this study, we aimed to investigate whether PD-L1/PD-L2 dKO has a protective effect on RGCs in a mouse model of chronic ocular hypertension (COHT). Methods: We used magnetic beads to induce COHT in mice. Apoptosis of RGCs and activation of microglia were evaluated using western blotting and immunofluorescence staining of the mouse retina. In addition, we also conducted transcriptome sequencing and further gene expression analyses using the Kyoto Encyclopedia of Genes (KEGG) database. Results: In the mouse model of COHT, PD-L1/PD-L2 dKO prevented the apoptosis of RGCs to some extent. Blocking the programmed cell death 1 (PD-1) pathway also increased the number of anti-inflammatory M2-activated microglia and enhanced the phosphorylation of its related pathway STAT6. Sequencing results showed that this protective effect may have been achieved by regulating the NF−B signaling pathway. Conclusion: Blocking the PD-1 pathway has a protective effect on RGCs in the mouse model of COHT induced by magnetic beads.